Introduction to International Futures - Pardee Center, International Futures (2016)
INTERNATIONAL FUTURES HELP SYSTEM Introduction to IFs Purposes Visual Representation of IFs Issues and Modules Quick Survey of IFs Issues an d Modules IFs Background IFs Geographic Representation of the World IF s Time Horizon Instructional Use Acknowledgements Feedback Support for IFs Use Development Mode Features